Polite Character from a Multicultural Perspective: A Systematic Literature Review - Zahra Nelissa; Agus Taufiq; Juntika Nurihsan; Anne Hafina; Khairiah Khairiah (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
The rise of globalization and increasing cultural diversity in modern societies pose complex challenges in shaping polite character, which is considered universal but varies significantly across cultures. This study aims to explore the characteristics of polite behavior from multiple cultural perspectives, evaluate its application in multicultural education, identify factors influencing its development, and investigate the integration of universal politeness with local cultural values. A qualitative approach was employed through a Systematic Literature Review (SLR) guided by the PRISMA protocol. Literature was sourced from Scopus and Google Scholar, focusing on Q1–Q4 journals published between 2020 and 2025 in Indonesian and English. The review of ten cross-cultural studies revealed diverse politeness strategies across regions from East Asia to Africa, highlighting ten influential factors, including cultural orientation, social status, relational closeness, and pragmatic competence. The findings show that politeness is not a fixed construct but a culturally contextual phenomenon, necessitating holistic and adaptive strategies in multicultural education. This study concludes that integrating universal values with cultural particularities requires intercultural pragmatic competence and culturally responsive pedagogy. These findings offer both theoretical and practical contributions to character education, emphasizing the importance of balancing global standards with local wisdom in fostering social harmony.